Human and Inhuman Transformations in Nancy Huston's Dystopian Novel Le Club des miracles relatifs. Issue 3 (December 2018) - Ireland, Susan; Proulx, Patrice J.
Abstract : Huston's Le Club des miracles relatifs takes up familiar themes from the author's corpus and transposes them into a disturbing dystopian tale about the destruction of the Earth and the devalorization of humanity in the tar sands of Alberta. Through its combination of speculative fiction and environmental literature, Huston's hybrid text attests to the creative dynamism of her œuvre. This essay examines the diverse types of mobility present in the text, from the physical migration of characters and the transformation of the natural environment to the recurrent use of intertextual references and the dialogue between the novel and the collection of essays in Brut: la ruée vers l'or noir . In particular, it explores the representation of the mining site as a translingual, transnational space and discusses the ways in which Huston depicts the social injustice resulting from environmental destruction as a negative form of progress.